2017
DOI: 10.1007/s00784-017-2061-y
|View full text |Cite|
|
Sign up to set email alerts
|

Early bone formation around immediately loaded implants with nanostructured calcium-incorporated and machined surface: a randomized, controlled histologic and histomorphometric study in the human posterior maxilla

Abstract: Under immediate loading conditions in the human posterior maxilla, the nanostructured calcium-incorporated surface has led to better histologic and histomorphometric results than the machined surface; therefore, the clinical use of implants with nanostructured calcium-incorporated surface may be beneficial in the posterior maxilla, under immediate loading protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 32 publications
2
43
0
Order By: Relevance
“…Several authors have suggested that primary stability may be a useful predictor for osseointegration [29][30][31][32][33][34][35] and that a high primary stability makes immediate loading more predictable [19,20,26,27] [32]. In fact, in that study, no implant with ISQ > 60 failed, while 19% of implants with ISQ < 60 failed [32].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Several authors have suggested that primary stability may be a useful predictor for osseointegration [29][30][31][32][33][34][35] and that a high primary stability makes immediate loading more predictable [19,20,26,27] [32]. In fact, in that study, no implant with ISQ > 60 failed, while 19% of implants with ISQ < 60 failed [32].…”
Section: Discussionmentioning
confidence: 90%
“…The surface of these implants was the result of a sandblasting treatment (resorbable blast media) and the subsequent incorporation of calcium ions by means of a hydrothermal treatment [28]. This nanotopographical surface (Xpeed5, Megagen, Gyeongsang, South Korea) is characterized by increased surface area/energy, for a better interaction with biological fluids, and therefore has the potential to stimulate and accelerate osseointegration [28,29]. Finally, from the prosthetic point of view, such fixtures possess a 5 mm deep conical connection (10 ∘ ) combined with an internal hexagon, capable of ensuring high mechanical stability and a suitable biological seal; an integrated switching platform is present, to maintain peri-implant tissue volume over time [19,20].…”
Section: Dental Implantsmentioning
confidence: 99%
“…With this procedure, a nanolayer of Ca 2+ ions is incorporated onto the RBM surface, giving a CaTiO 3 nanostructure. Previous studies [24,32,33] have reported the following standard roughness parameters for this surface: a mean Ra (the arithmetic mean of the absolute height of all points) of 1.6 (±0.2) µm, a mean Rq (the square root of the sum of the squared mean difference of all points) of 2.1 (±0.3) μm, and a mean Rt (the difference between the highest and lowest points) of 15.7 (±0.2) μm. …”
Section: Methodsmentioning
confidence: 99%
“…The Xpeed ® surface (Megagen, Seoul, South Korea) is a nanostructured surface enriched with calcium ions through a hydrothermal method [24,32,33]. Histological and histomorphometrical studies on humans have confirmed that this nanostructured surface can support new bone formation, under an immediate loading protocol [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation